Water efficiency management strategies for airports - Krop, Richard A., 1962-; Young, Michelle L.; Jolley, James; Davis, William (ACRP report, 2016)
TRB's Airport Cooperative Research Program (ACRP) Report 154: Water Efficiency Management Strategies for Airports provides a guidebook and tools that airport operators can use to design and institute a water efficiency management program specific to their facility. The report enables airport operators to understand water uses and usage at airports to generate a baseline water use profile specific to their airport activities, and to define appropriate water use targets. It will also help operators evaluate appropriate water efficiency measures, including their direct and indirect costs and benefits that can be used to develop a water efficiency management action plan. The report addresses water management tools and practices used worldwide within and outside of the airport industry; methods for collection, management, and analysis of data relevant to airport water management; collaboration and communication with the public and stakeholders, including water providers; program implementation strategies, including motivation for decision makers; infrastructure operation and maintenance considerations; and drought planning considerations. Additional materials that accompany the report include the End Use Water Audit Tool, which can be used to estimate an airport baseline water footprint, and a PowerPoint presentation, which provides an overview of the guidebook and the toolbox.